Blend uniformity validation in low dose formulation of levocetirizine hydrochloride tablet - K. Kathiresan, (IJPAR JOURNAL, 2016)
One of the most challenging problems conformations oral solid dosage form manufacturers today is the difficulty in applying scientifically valid methods to blend uniformity validation. Validation of final blending process, as one of a series of unit operations, is important to ensure satisfactory active ingredient content in a tablet, in particular, in low dose formulations. Routine final blend evaluation for active ingredient homogeneity is unwarranted, although it may be appropriate in certain circumstances. However, the final product (e.g. tablets, capsules) is required to be tested for the uniformity of dosage units to meet the Pharmacopoeia requirements. In this work, the blend uniformity is validated in a low dose tablet formulation to the predetermined protocols as part of concurrent process validation. The selected product is Levocetirizine Hcl (Each tablet contains Levocetirizine Hcl 5 mg).The test for content uniformity is applicable to this product as per requirement of BP / USP / IP, hence the study is conducted to assure the compliance to official requirements of content uniformity in the product by demonstrating adequate blend uniformity during the mixing operation.